2020
DOI: 10.3889/oamjms.2020.4330
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Medication Errors in a Tertiary Care Hospitals in the Qassim Region, Saudi Arabia

Abstract: BACKGROUND: Medication errors (MEs) have been defined as “any preventable event that may cause or lead to inappropriate medication or patient harm when the medication is in the control of the health care professional, patient, or consumer.” AIM: The aim of this study is to identify, analyze, and compare the common types of errors encountered in prescriptions, as well as the factors associated with the root causes of these errors, in a large tertiary hospital in the Qassim region of Saudi Arabia.&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…The prevalence of medication error was 72.1%, and only 41.2% of the total were reported. This result highlights the high risk of medication error among nurses in Saudi Arabia, aligning with prior research in which nurses were responsible for 31.0% and 35.0% of medication errors recorded from retrospective and cross-sectional data in the country [14,15]. Moreover, the incidence of medication errors was 44.4% in Saudi Arabia hospitals with prescribing and administration errors as the most frequently reported medication errors [12].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The prevalence of medication error was 72.1%, and only 41.2% of the total were reported. This result highlights the high risk of medication error among nurses in Saudi Arabia, aligning with prior research in which nurses were responsible for 31.0% and 35.0% of medication errors recorded from retrospective and cross-sectional data in the country [14,15]. Moreover, the incidence of medication errors was 44.4% in Saudi Arabia hospitals with prescribing and administration errors as the most frequently reported medication errors [12].…”
Section: Discussionsupporting
confidence: 84%
“…Meanwhile, Alshammari et al [13] conducted a cross-sectional study among healthcare professionals and reported limited reporting of medication errors, and most participants lacked good knowledge of medication error stages and had no history of being trained on the issue. The only study that presented information regarding medication errors among nurses was performed by Harkan et al [14]. The authors conducted a retrospective cross-sectional analysis in tertiary healthcare facilities in the Al-Qassim region of the KSA and found that medication errors by physicians and nurses accounted for 60.4% and 34.0% of the overall errors.…”
Section: Introductionmentioning
confidence: 99%
“…However, this solution provides excessive information, which was time-consuming. Furthermore, it does not fulfill the nurses' needs for a quick review of the most common medications used in a specific unit [5]. Another solution was adding a feature that categorizes the medication into top general common medications or according to a specific disease and not for units or conditions requiring a quick reaction [6].…”
Section: Problem Statementmentioning
confidence: 99%
“…When giving medications, nurses should remember "five rules" and take them into account all the time: the right medication, the right patient, the right dose, the right time, and the right way [5]. Among the main causes of medication errors is exposure to distraction.…”
Section: Requirement Specificationmentioning
confidence: 99%
See 1 more Smart Citation